(untitled) (Bangladesh Journal of Agricultural Research, 2016)
In vitro cormel development in Mukhi Kachu (Colocasia esculenta) Var. Bilashi was assessed in an experiment using three levels of BAP (0, 5 and 10 mg/l) and four levels of sucrose (0, 5, 10 and 15 %). Individual shoot excised from multiple shoot was used as explant in this experiment. In vitro cormel formation of Colocasia is an important means of organogenesis, which initiated earlier with 10% sucrose in 15% culture, whereas 15% sucrose produced cormels in 50% culture. While BAP at 10 mg/l formed cormels in 32.5% cultures but these two factors together formed cormels in 85% cultures, having 2.5 cormel per culture. The cormel weighed upto 1.7 g and contained 81.5% dry matter. Bangladesh J. Agril. Res. 40(4): 601-606, December 2015